Nephrotoxicity of hump-nosed pit viper (Hypnale hypnale) venom in mice is preventable by the paraspecific Hemato polyvalent antivenom (HPA) - Tan, C.H.; Tan, N.H.; Sim, S.M.; Fung, S.Y.; Jayalakshmi, P.; Gnanathasan, C.A. (2012)
Mice experimentally envenomed with Hypnale hypnale venom (1 x and 1.5x LD50) developed acute kidney injury (AKI) principally characterized by raised blood urea and creatinine. Prolonged blood clotting time and hemorrhage in lungs implied bleeding tendency. Pallor noted in most renal cortices was suggestive of renal ischemia secondary to consumptive coagulopathy. Intravenous infusion of Hemato polyvalent antivenom following experimental envenoming effectively prevented death and AKI in all mice, supporting its potential therapeutic use in envenoming cases. (C) 2012 Elsevier Ltd. All rights reserved.